Phase II evaluation of capecitabine in refractory nonsquamous cell carcinoma of the cervix: a Gynecologic Oncology Group Study. Issue 4 (1st July 2008) - Look, K. Y.; Blessing, J. A.; Michener, C. M.; Rubin, S. C.; Ramirez, P. T.
Abstract : We conducted a multi-institutional study to assess the activity and toxicity of capecitabine in patients with persistent or recurrent nonsquamous cancer of the cervix. Eligible patients were required to possess adequate renal, hepatic and bone marrow function and a Gynecologic Oncology Group performance status of 0–2. Histologic confirmation of the original primary cancer was mandated. Patients must have received one prior systemic chemotherapeutic regimen for cervical cancer that did not include the chemotherapy that may have been administered in conjunction with prior radiation therapy. The initial dose schedule was 2500 mg/m 2 orally daily in two divided doses for 14 consecutive days, followed by a 7-day rest, such that each cycle was 21 days. Responses were assessed using response evaluation criteria in solid tumors. Twenty-one patients were entered into the trial. One patient was declared ineligible for wrong cell type; thus, 20 were evaluable for toxicity. A median of 2.5 cycles was administered (range 1–11). There was one septic death. Grade 4 neutropenia, renal, neurologic, and pulmonary toxicity was seen in 5%, 5%, 5%, and 10% patients, respectively. There were no responses. Nine patients (45%) each had stable disease and nine showed progression. The remaining two cases (10%) did not have subsequent disease assessment and response could not be assessed. Oral capecitabine at the dose and schedule tested has insignificant activity in nonsquamous cervical cancer patients previously treated with chemotherapy.